FAMILY THERAPY DALAM MENANGANI POLA ASUH ORANG TUA YANG SALAH PADA ANAK SLOW LEARNER (Jurusan Bimbingan dan Konseling Islam, 2013)
Some parents had erred in foster patterns of children who have lacked the slow learner. Usually they let the kids out of school. And without realizing it suddenly became increasingly unruly children. Under such background, this paper raised about Family therapy in dealing with wrong parenting skill of parents on slow learner child. That is about how the application of family therapy as a result. In this study, researchers using qualitative research methods, case study research with descriptive comparative analysis to know the flow of the problems experienced by children and to compare the child's condition before and after the treatment. Later, the application of this family therapy process consists of several steps that collect and organize information about the family and see the relationships that occur within a family. After that, researcher make the homework activity that is gathering the family to communicate well with each other to solve problems together.Keywords: Family Therapy, Parenting, Slow Learner